Factors Influencing Motivation for Examination Visual Inspection with Uric Acid Acetate (IVA TEST) in Health Workers at UPT Puskesmas Barong Tongkok - Munawarah; Lukman Nurhakim; Siti Raihanah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the factors related to the motivation of women of childbearing age to carry out IVA examinations among health workers at the UPT Puskesmas Barong Tongkok. This type of research is analytic observational with a cross sectional approach. The population in this study were all women of childbearing age (age 15-49 years) who worked as health workers at the UPT Puskesmas Barong Tongkok, a total of 30 people. Sampling in this study using total sampling technique. Data analysis technique used the chi square test and multivariate analysis using logistic regression. The results of the study found that there were factors related to the motivation of women of childbearing age to carry out Acetic Acid Visual Inspection (IVA) examinations for health workers at the UPT Puskesmas Barong Tongkok including knowledge, attitudes, information that had been obtained, husband support, support for health workers, and psychological level of anxiety.